More Than a Waltz ImPulsTanz round-up - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2008)
ImPulsTanz round-up. ImPulsTanz celebrated its twenty-fifth anniversary in 2008 with a presence and status across Vienna that might make other dance festivals jealous.